Libraries in the Age of Intelligent Information: AI-Driven Solutions - Baber, Mehranullah; Islam, Kanwal; Ullah, Adnan; Ullah, Wahid (MultiTech Publisher, 2024)
This study explores the paradigm change that artificial intelligence (AI) has brought about in the context of libraries in the age of intelligent information. A quantitative survey was carried out, and a methodical description of the study's procedure is provided. The research sampling strategy, data gathering, data collection tool, and statistical analysis are all included in this quantitative approach. Additionally, a random sampling procedure was used to choose the study sample. Similar to this, questionnaires were employed as response instruments to collect data in both physical and digital formats. Findings from the investigation showed that 45% of institutions are private nature and 50% institutions shows the status public. 1-10 years’ experience were 62% respondents, 11-20 years’ experience were 31% and only 8% of respondents were 21 years above experience. The study emphasizes how important it is to create a welcoming and open library ecosystem where artificial intelligence (AI) enhances operational effectiveness while protecting user privacy and pleasure. All things considered, this thorough analysis highlights the many ways that artificial intelligence (AI) might transform libraries and meet the many demands of their patrons. Looking forward, the article discusses the promising future of AI in libraries, envisioning AI-powered chatbots, predictive analytics, and virtual helpers as integral components of an AI-driven library landscape.